Gamification in agriculture: A scoping study on opportunities and challenges - Oberoi, Zeena; Vyas, Shalika; Kropff, Wietske; Girvetz, Evan Hartunian (2023)
This document outlines a landscape analysis of Busara in Partnership with CGIAR, of potential scenarios where gamification could be applied in East and Southern Africa in Agriculture.